Seasonal Impacts of Solar UV Radiation on Photosynthesis of Phytoplankton Assemblages in the Coastal Waters of the South China Sea - Wu, Yaping; Gao, Kunshan; 高坤山; Li, Gang（ CAS, S China Sea Inst Oceanol, Key Lab Marine Bio Resources Sustainable Utilizat, Guangzhou, Guangdong, Peoples R China）; Walter Helbling, Eduardo（Consejo Nacl Invest Cient & Tecn, Chubut, Argentina） (Photochemistry and Photobiology, 2010)
We carried out experiments to evaluate seasonal changes in the impacts of UV radiation (UVR, 280-400 nm) on photosynthetic carbon fixation of phytoplankton assemblages. Surface water samples were obtained in the coastal area of the South China Sea, where chlorophyll a ranged 0.72-3.82 mu g L-1. Assimilation numbers (photosynthetic carbon fixation rate per chl a) were significantly higher during summer 2005 than those in spring and winter 2004. The mean values obtained under photosynthetically active radiation (PAR) were 2.83 (spring 2004), 4.35 (winter 2004) and 7.29 mu g C (mu g chl a)-1 h-1 (summer 2005), respectively. The assimilation numbers under PAR + UVR were 1.58, 2.71 and 5.28 mu g C (mu g chl a)-1 h-1, for spring, winter and summer, respectively. UVR induced less inhibition of photosynthesis during summer 2005 than during the other seasons, in spite of the higher UVR during summer. The seasonal differences in the productivity and photosynthetic response to UV were mainly due to changes in water temperature, while irradiance and vertical mixing explained > 80% of the observed variability. Our data suggest that previous studies in the SCS using UV-opaque vessels might have overestimated the phytoplankton production by about 80% in spring, 61% in winter and 38% in summer. National Natural Science Foundation of China [40930846, 40876058]; Ministry of Education [308015]